PERBANDINGAN MEDIA PEMBELAJARAN AUDIOVISUAL DARI YOUTUBE PADA SUBTEMA PEREDARAN DARAHKU SEHAT KELAS V SD NEGERI 100 PALEMBANG - Wili Kasvili; Marwan Pulungan; Nuraini Usman (Universitas Sriwijaya, 2021)
This study aims to compare similarities and differences about the learning video. This type of research is descriptive qualitative analysis research. The subject of this study was observing a learning video, one of the teachers of Grade V.A SD Negeri 100 Palembang with a learning video from Youtube. This research was conducted in the odd semester of the 2020- 2021 school year. Data analysis in this study using observation sheets and interviews. In terms of the content of learning materials have been well used for students both teacher videos and videos from Youtube, the use of music in the teacher's video and Youtube has used musical instruments with a low voice followed by voice over. Even though both the teacher's video and the video made by the creator on Youtube still have some shortcomings but not too fatal such as the error of the word and display the face of the narrator. teacher-made learning videos and learning videos from Youtube to the whole have been good to be used in learning although there are some parts that must be improved in the future so that the learning videos made more interesting, easy to understand and effective. Keywords: Analysis, Learning Videos, Comparison